Managing risk : methods for software systems development - Hall, Elaine M. (Reading, MA : Addison-Wesley, 1998)
'Written for busy professionals charged with delivering high-quality products on time and within budget, Managing Risk is a comprehensive guide that describes a success formula for managing software risk. The book is divided into five parts that describe a risk management road map designed to take you from crisis to control of your software project.''Highlights include six disciplines for managing product development, steps to predictable risk management process results, how to establish the infrastructure for a risk-aware culture, methods for the implementation of a risk management plan, and case studies of people in crisis - and in control.'--BOOK JACKET.
Pt. I. Risk Management Discovery. Ch. 1. Software Risk Management. Ch. 2. P[superscript 2]I[superscript 2] Success Formula. Ch. 3. Risk Management Map -- Pt. II. Risk Management Process. Ch. 4. Identify Risk. Ch. 5. Analyze Risk. Ch. 6. Plan Risk. Ch. 7. Track Risk. Ch. 8. Resolve Risk -- Pt. III. Risk Management Infrastructure. Ch. 9. Develop the Policy. Ch. 10. Define Standard Process. Ch. 11. Train Risk Technology. Ch. 12. Verify Compliance. Ch. 13. Improve Practice -- Pt. IV. Risk Management Implementation. Ch. 14. Establish the Initiative. Ch. 15. Develop the Plan. Ch. 16. Tailor the Standard Process. Ch. 17. Assess Risk. Ch. 18. Control Risk -- Pt. V. People in Crisis and Control. Ch. 19. Stage 1: Problem. Ch. 20. Stage 2: Mitigation. Ch. 21. Stage 3: Prevention. Ch. 22. Stage 4: Anticipation. Ch. 23. Stage 5: Opportunity.
Includes bibliographical references and index.
Also issued online.
Keywords: Computer software; Risk management; Computer software -- Development